Semantic Errors Analysis of Consumer Perception in Social Media Advertising and ITS Relevance to Indonesian Language Learning - Wahyuni Rizeki; Wini Marzatillah; Maulidia; Syarafina Dwita; Shahiratul Ula; Dara Syakila; Lina Sundana (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze semantic errors in social media advertisements and their impact on consumer perceptions. Semantic errors, in this context, refer to the use of words, phrases, or sentences that are inaccurate or ambiguous, which can impact consumer understanding and response to a product or service. The method used was descriptive qualitative with a content analysis approach to several social media advertisements distributed on platforms such as Instagram, TikTok, and Facebook. The analysis results indicate that semantic errors, such as the use of non-standard words, ambiguous meanings, and deviations from meaning, are common and impact consumers' misinterpretation of information. Furthermore, this study also examines the relevance of this phenomenon in the context of Indonesian language learning, particularly in strengthening semantic competence and good and correct language skills.